The management of central post-stroke pain. - Bowsher, D. (BMJ Group, 1995)
Central post-stroke pain (CPSP) used to be known as 'thalamic syndrome'. Early post-mortem studies showed that many cases had extrathalamic lesions, and modern imaging methods have confirmed and extended these findings. CPSP affects between 2 and 6% of stroke patients, ie, there is an annual incidence in the UK of between 2000 and 6000. Most patients with CPSP appear to be younger than the general stroke population, and usually to have relatively mild motor affliction; thus they may live for many years, giving a prevalence perhaps as high as 20,000. True CPSP, characterised by a partial or total deficit for thermal and/or sharpness sensations, is best treated initially with adrenergically active antidepressants. If these do not work, mexiletine may be added in suitable cases. Recent studies suggest that stimulation of the motor cortex or spinal cord by implanted electrodes may help patients resistant to medical treatment. Positive relaxation, as an adjuvant therapy, should be used in nearly all cases. Considerable or even total relief can be achieved in almost two thirds of patients. There is evidence that the sooner antidepressant treatment is begun, the more likely the patient is to respond; time should not be wasted trying conventional analgesics, which rarely have any significant effect.